1977
DOI: 10.2134/jeq1977.00472425000600020011x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of 2,4‐D Load in Surface Runoff Down a Grassed Waterway

Abstract: The effectiveness of a grassed waterway in decreasing 2,4‐D [(2,4‐dichlorophenoxy) acetic acid] content in surface runoff was investigated. Corn (Zea mays L.) plots were treated with 2,4‐D (0.56 kg/ha) and runoff produced by applying simulated rain was directed through a 24.4‐m‐long grassed waterway. The 2,4‐D concentrations were measured under wet and dry antecedent waterway and plot conditions. Reduction in 2,4‐D load in waterways results from water loss by infiltration, sediment loss, and by attachment‐abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…Dense, low-growing grasses are used to stabilize and protect the soil surface against erosion by concentrated runoff (Dosskey, 2001). To serve this function effectively, there is usually a selection of fast growing grasses which are mowed frequently in order to prevent sward-damaging sedimentation and to reduce hydraulic roughness (Ree, 1949;Asmussen et al, 1977;Fiener and Auerswald, 2003). Also, grassed waterways reduce the velocity of overland flow and reduce peak discharge rate (Chow et al, 1999).…”
Section: Prevention Of Pesticide Input In Water Bodiesmentioning
confidence: 99%
“…Dense, low-growing grasses are used to stabilize and protect the soil surface against erosion by concentrated runoff (Dosskey, 2001). To serve this function effectively, there is usually a selection of fast growing grasses which are mowed frequently in order to prevent sward-damaging sedimentation and to reduce hydraulic roughness (Ree, 1949;Asmussen et al, 1977;Fiener and Auerswald, 2003). Also, grassed waterways reduce the velocity of overland flow and reduce peak discharge rate (Chow et al, 1999).…”
Section: Prevention Of Pesticide Input In Water Bodiesmentioning
confidence: 99%
“…Since VFSs are commonly placed near streams and these areas can suffer seasonal shallow water conditions, this tool fills an important gap in environmental management and analysis. For example, in Europe VFSs are often prescribed along river drainage networks without objective assessment of their efficiency during winter wet periods (Carluer et al, 2017;Bach et al, 2017). In the US, the historical topography-based approach, which links priority for buffers to locations where runoff water converges from uplands and saturates the soil, often results in placement on bottomlands next to streams (Dosskey and Qiu, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Grass buffer zones or vegetative filter strips (VFSs), are a typical environmental control practice to protect aquatic ecosystems from sediment, and agrichemicals from agricultural fields (Roberts et al, 2012). While VFSs are recommended in the USA and other regions, in Europe they are often mandatory along rivers due to their potential to limit surface pesticide runoff and aerial spray drift from entering adjacent surface water bodies (Asmussen et al, 1977;Rohde et al 1980;USDA-NRCS, 2000;Dosskey, 2001;Syversen and Bechmann, 2004;Poletika et al, 2009). However, the effectiveness of edge-of-field buffer strips to…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using simulated rainfall on 24.4 m long waterways, Asmussen et al (1977) found that total losses of 2,4-D were 2.5 and 10.3% for dry and wet plots, respectively. Rhode et al (1980) found higher herbicide reduction in buffer strips during dry soil conditions.…”
Section: Conditions Of Each Surface Flow Simulation Are Presented Inmentioning
confidence: 99%